Analysis Of Kpk Policy On Corruption Eradication In Indonesia In The Review Of The Corruption Criminal Law - Pradini, Auly; Susanti, Emilia (Fakultas Hukum Dehasen, 2025)
Eradication of corruption is still the focus of law enforcement agencies in Indonesia. The Corruption Eradication Commission (KPK) was formed based on Law Number 30 of 2002 to spearhead the eradication of corruption in Indonesia. The Corruption Eradication Commission is given greater authority in handling corruption cases than other law enforcement agencies, especially the police and the prosecutor's office. Based on data from Law Enforcement Statistics, the KPK has handled 1,135 corruption cases since its establishment, starting from handling cases in 2004 to publication at the end of December 2018. Evidently, the focus of this article is the direction of the anti-corruption policy of the Indonesian Corruption Eradication Commission.